2023
DOI: 10.1002/anie.202315457
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Zwitterionic Hemicyanine Reporters for Early Diagnosis and Prognostic Assessment of Acute Renal Failure

Ya Zhou,
Lijuan Zhu,
Biaoxiang Liu
et al.

Abstract: Drug‐induced renal failure (DIRF) poses a serious medical complication with high mortality risk. However, early diagnosis or prognosis of DIRF remain challenging, as current methods rely on detecting late‐stage biomarkers. Herein we present a library of zwitterionic unimolecular hemicyanines (ZCs) available for constructing activatable reporters to detect DIRF since its initial stage. Zwitterionic properties of these probes are achieved through interspersedly integrating alkyl sulfonates and quaternary ammo‐ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It also offers potential for remote DIRF detection and prediction of renoprotective efficacy through optical urinalysis. 41…”
Section: Molecular Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…It also offers potential for remote DIRF detection and prediction of renoprotective efficacy through optical urinalysis. 41…”
Section: Molecular Imagingmentioning
confidence: 99%
“…This enabled sensitive detection of intrarenal apoptosis 60 h earlier than clinical methods, allowing for precise evaluation of apoptosis remediation effects. It also offers potential for remote DIRF detection and prediction of renoprotective efficacy through optical urinalysis …”
Section: Classification Of Fluorescent Probesmentioning
confidence: 99%
“…38 Other studies by Zhou and Liu have demonstrated the competitive photodynamic effects of asymmetric NIR-II PSs, suggesting that the asymmetric strategy is a promising approach for designing novel PSs with NIR-II emission. 55,56…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the in-depth understanding of the transport and interaction mechanisms of molecules/nanoparticles in the kidney 11,12 NIR fluorescence imaging probes (Table S1), such as ultrasmall gold nanoparticles (GS-AuNPs, 13,14 GNP-KTP5-ICG 15 ) and a series of activatable molecular probes (MRPs, 16 ADR, 17 CDIR2, 18 NCRs, 19 FPRR, 20 1-DPA2, 21 and ACRR 22 ). These probes not only clear rapidly from the kidneys but also have the capability to detect kidney dysfunction with substantially enhanced kidney contrast and minimized background signal interference.…”
Section: Introductionmentioning
confidence: 99%